Lung Volume Reduction Surgery Reduces Pulmonary Arterial Hypertension Associated With Severe Lung Emphysema and Hypercapnia. Issue 2 (12th April 2022) - Akil, Ali; Ziegeler, Stephan; Rehers, Stephanie; Lavae-Mokhtari, Mahyar; Richter, Lars; Dickgreber, Nicolas Johannes; Ernst, Erik Christian; Fischer, Stefan
Abstract : Lung volume reduction surgery (LVRS) represents a standard surgical approach for patients with severe pulmonary emphysema. One of the relevant risk factors for LVRS is the presence of pulmonary arterial hypertension (PAH). The aim of this study is to assess the postoperative changes in pulmonary arterial pressure (PAP) after LVRS for patients with severe pulmonary emphysema compared with preoperative measures. N = 61 consecutive patients with severe pulmonary emphysema and preoperative evidence for PAH (pulmonary arterial systolic pressure [PASP] ≥ 35 mmHg) were prospectively included into this study. In all patients, thoracoscopic LVRS was performed. PASP was assessed by echocardiography before surgery, early postoperatively, and 3 months after surgery. Data were prospectively recorded and analyzed retrospectively. Primary end points were the postoperative changes in PASP as well as the 90 day mortality rate. Secondary endpoints included: pulmonary function test, exercise capacity, quality of life, and dyspnea symptoms (Borg scale). Early after surgery, a significant reduction in PASP was observed at the day of discharge and at 3 month follow-up. In n = 34 patients, no tricuspid valve regurgitation was detectable anymore suggesting normal PAP. In n = 3 patients, venovenous extracorporeal lung support (VV ECLS) was already implemented preoperatively. In the remaining cases, VV ECLS was applied intraoperatively and continued postoperatively. Mean duration of postoperative ECLS support was 2 days. Four patients died due to acute right heart failure, two patients from sepsis with multiorgan failure, and one patient from acute pulmonary embolism. Ninety day mortality was 11.5 %. A significant improvement was postoperatively observed regarding the performance status, dyspnea scale, as well as quality of life. This study suggests a beneficial effect of LVRS on PAP, which may ultimately help to protect and stabilize right ventricular function. Further studies, implementing pre- and postoperative right heart catheterizations including invasive PAP evaluation, are necessary to support the findings in this study in greater detail.